Effect of Ag doping on the structural, electrical and optical properties of ZnO grown by MOCVD at different substrate temperatures. (May 2018) - Ievtushenko, A.; Karpyna, V.; Eriksson, J.; Tsiaoussis, I.; Shtepliuk, I.; Lashkarev, G.; Yakimova, R.; Khranovskyy, V.
Abstract: ZnO films and nanostructures were deposited on Si substrates by MOCVD using single source solid state zinc acetylacetonate (Zn(AA)) precursor. Doping by silver was realized in-situ via adding 1 and 10 wt. % of Ag acetylacetonate (Ag(AA)) to zinc precursor. Influence of Ag on the microstructure, electrical and optical properties of ZnO at temperature range 220–550 °C was studied by scanning, transmission electron and Kelvin probe force microscopy, photoluminescence and four-point probe electrical measurements. Ag doping affects the ZnO microstructure via changing the nucleation mode into heterogeneous and thus transforming the polycrystalline films into a matrix of highly c -axis textured hexagonally faceted nanorods. Increase of the work function value from 4.45 to 4.75 eV was observed with Ag content increase, which is attributed to Ag behaviour as a donor impurity. It was observed, that near-band edge emission of ZnO NS was enhanced with Ag doping as a result of quenching deep-level emission. Upon high doping of ZnO by Ag it tends to promote the formation of basal plane stacking faults defect, as it was observed by HR TEM and PL study in the case of 10 wt.% of Ag. Based on the results obtained, it is suggested that NS deposition at lower temperatures (220–300 °C) is more favorable for p -type doping of ZnO. Highlights: Undoped and Ag-doped ZnO films and nanostructures were grown. Ag doping has caused the ZnO nanostructures growth via changing the nucleation mode. High Ag doping of ZnO leads to formation of basal plane stacking faults defect. Near-band edge emission of ZnO nanostructures was enhanced with Ag doping. Growth at lower temperatures is more favorable for ZnO p -type doping.